BioNLP 2017 2017
DOI: 10.18653/v1/w17-2334
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Feature Extraction Methods for Knowledge-based Biomedical Word Sense Disambiguation

Abstract: In this paper, we present an analysis of feature extraction methods via dimensionality reduction for the task of biomedical Word Sense Disambiguation (WSD). We modify the vector representations in the 2-MRD WSD algorithm, and evaluate four dimensionality reduction methods: Word Embeddings using Continuous Bag of Words and Skip Gram, Singular Value Decomposition (SVD), and Principal Component Analysis (PCA). We also evaluate the effects of vector size on the performance of each of these methods. Results are eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Unsupervised methods do not require labeled training examples and typically use graph-based clustering techniques [15]. Recently, word embedding models [16] and pre-trained language model BERT (Bidirectional Encoder Representation from Transformers) [17], [18] and its variant BERT models [19], [20], [21] all pre-trained on large corpora were introduced to conduct unsupervised learning for WSD. For example, Mao and Wah [6] generate semantic relatedness measurements between UMLS concepts to achieve disambiguation by applying the word embedding models and various flavors of BERT.…”
Section: Previous Workmentioning
confidence: 99%
“…Unsupervised methods do not require labeled training examples and typically use graph-based clustering techniques [15]. Recently, word embedding models [16] and pre-trained language model BERT (Bidirectional Encoder Representation from Transformers) [17], [18] and its variant BERT models [19], [20], [21] all pre-trained on large corpora were introduced to conduct unsupervised learning for WSD. For example, Mao and Wah [6] generate semantic relatedness measurements between UMLS concepts to achieve disambiguation by applying the word embedding models and various flavors of BERT.…”
Section: Previous Workmentioning
confidence: 99%
“…The YTEX suite of algorithms [103,104] extends both MetaMap and cTAKES with a disambiguation module that helps to reduce noise considerably, although [105] found that it often over-filtered correct concepts. There has also been significant research in recent years on developing standalone models for disambiguation, using co-occurrence and feature-based approaches [106][107][108] as well as neural models [37,109]. Medical concept normalization more broadly has also become an increasing research focus [38,15], with significant opportunities for disambiguation research [21].…”
Section: Opportunities For Disambiguation Research Using Semantic Typ...mentioning
confidence: 99%
“…While some of the deep learning models directly employ word embeddings for disambiguation (Wu et al, 2015;Antunes and Matos, 2017;Charbonnier and Wartena, 2018;Ciosici et al, 2019), some of them employ deep architectures to encode the context of the acronym (Jin et al, 2019;Li et al, 2019). Moreover, acronym disambiguation has been also modeled as the more general tasks Word Sense Disambiguation (WSD) (Henry et al, 2017;Tulkens et al, 2016) or Entity Linking (EL) (Cheng and Roth, 2013;Li et al, 2015). While the majority of the prior work studies AD in medical domain (Okazaki and Ananiadou, 2006;Vo et al, 2016;Wu et al, 2017), recently some work proposes acronym disambiguation in general (Ciosici et al, 2019), enterprise (Li et al, 2018), or scientific domain (Charbonnier and Wartena, 2018).…”
Section: Related Workmentioning
confidence: 99%